2018
DOI: 10.3389/fmed.2018.00070
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Central Nervous System Infiltration by Myeloid and Lymphoid Hematologic Neoplasms Using Flow Cytometry Analysis: Diagnostic Accuracy Study

Abstract: IntroductionInfiltration of the central nervous system (CNS) by hematologic or lymphoid malignant cells can cause extensive neurological damage, be progressive and fatal. However, usually, the cerebrospinal fluid (CSF) has low cellularity and rapid cell degeneration, which can impair cytometry analysis. Storage and transport measures, sample preparation, and staining protocols can interfere with diagnostic accuracy.ObjectiveTo calculate the diagnostic performance of flow cytometry (FC) using a cell stabilizer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In a series of 246 patients affected with DLBCL and 80 affected with BL, Wilson et al (2014) confirmed the superiority of MFC over CC. Therefore, MFC appears an excellent candidate, better than CC, to handle specimens such as CSF characterized by a “scarce event” situation (Bento et al, 2018; Craig et al, 2011; Nückel et al, 2006). This peculiarity was confirmed in pediatric ALL patients in whom MFC was able to ameliorate significantly the demonstration of occult CSF involvement (Popov et al, 2019; Swinburne et al, 2019).…”
Section: Clinical Significance Of “Occult Cns Disease”mentioning
confidence: 99%
“…In a series of 246 patients affected with DLBCL and 80 affected with BL, Wilson et al (2014) confirmed the superiority of MFC over CC. Therefore, MFC appears an excellent candidate, better than CC, to handle specimens such as CSF characterized by a “scarce event” situation (Bento et al, 2018; Craig et al, 2011; Nückel et al, 2006). This peculiarity was confirmed in pediatric ALL patients in whom MFC was able to ameliorate significantly the demonstration of occult CSF involvement (Popov et al, 2019; Swinburne et al, 2019).…”
Section: Clinical Significance Of “Occult Cns Disease”mentioning
confidence: 99%
“…Neuroimaging by MRI or other techniques, although quite sensitive, have limited specificity. Cytomorphologic examination of the CSF is considered the “gold standard” for CNS involvement by haematologic malignancy due to its high specificity, although with limited sensitivity 5,7 …”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of the CNS by lymphoid malignancies can cause extensive neurological damage, be progressive and fatal. Meningeal infiltration by neoplastic cells occurs in approximately 5%‐15% of patients with leukaemia and lymphoma 3 . Involvement of the central nervous system by ALCL has been reported in less than 3% of all cases 4 .…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the low cellularity and rapid cell degeneration, establishing such a cytomorphologic diagnosis is often challenging. Additionally, storage and transport measures, sample preparation, and staining protocols can interfere with the diagnostic accuracy 3 …”
Section: Discussionmentioning
confidence: 99%